2019
DOI: 10.1002/ajmg.b.32726
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutamate receptors in attention‐deficit/hyperactivity disorder: From physiology to disease

Abstract: Attention-deficit hyperactivity disorder (ADHD) is the most common psychiatric disorder in children and adolescents, which is characterized by behavioral problems such as attention deficit, hyperactivity, and impulsivity. As the receptors of the major excitatory neurotransmitter in the mammalian central nervous system (CNS), glutamate receptors (GluRs) are strongly linked to normal brain functioning and pathological processes. Extensive investigations have been made about the structure, function, and regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 131 publications
0
21
0
1
Order By: Relevance
“…Many studies show increased DAT binding in ADHD patients [65,66]. Furthermore, ADHD has been associated with variants in DA receptors, 5-HT transporters and receptor subunits, and glutamate receptors [67][68][69]. A high percentage of adults suffering from ADHD report sleep problems and have a later chronotype, which might arise from the disorder itself or, in turn, aggravate it [70,71].…”
Section: Attention-deficit Hyperactivity Disordermentioning
confidence: 99%
“…Many studies show increased DAT binding in ADHD patients [65,66]. Furthermore, ADHD has been associated with variants in DA receptors, 5-HT transporters and receptor subunits, and glutamate receptors [67][68][69]. A high percentage of adults suffering from ADHD report sleep problems and have a later chronotype, which might arise from the disorder itself or, in turn, aggravate it [70,71].…”
Section: Attention-deficit Hyperactivity Disordermentioning
confidence: 99%
“…Physiologically, numerous avenues have been examined for a potential role in ADHD. One theory holds that ADHD involves changes in the glutaminergic neurotransmitter systems, a major excitatory pathway in the brain, however genome-wide SNP analysis has so far failed to identify glutamate receptor DNA variants as a significant association with ADHD [ 5 ]. Several lines of evidence, including the utility of drugs such as methyphenidate, amphetamines, and atomoxetine has suggested that deficits in the dopaminergic and adrenergic systems could underlie the neurochemical basis of ADHD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One theory holds that ADHD involves changes in the glutaminergic neurotransmitter systems, a major excitatory pathway in the brain, however genome-wide SNP analysis has so far failed to identify glutamate receptor DNA variants as a significant association with ADHD [5]. Several lines of evidence, including the utility of drugs such as methyphenidate, amphetamines, and atomoxetine has suggested that deficits in the dopaminergic and adrenergic systems could underlie the neurochemical basis of ADHD [6].…”
Section: Introductionmentioning
confidence: 99%